2009
DOI: 10.1590/s0100-54052009000100008
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade patogênica do fungo Pyricularia grisea no Estado de São Paulo

Abstract: Blast samples were collected during [2004][2005][2006] in different rice growing regions in São Paulo State, Brazil. The 71 monosporic isolates of Pyricularia grisea obtained were grouped into physiologic races based on the reaction type on a set of eight international and nine japanese differentials. Twenty-one pathotypes were identified among the 71 blast isolates according to the international set. The IB, ID and IG groups were most frequently detected (23, 21 an 17 times each, respectively). The virulence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
1
0
3
Order By: Relevance
“…No Estado de São Paulo, constataram-se 21 raças fisiológicas de M. grisea de um total de 71 isolados monospóricos, sendo as raças fisiológicas mais prevalentes pertencentes aos grupos IB e ID, com frequências de 32 e 30% dos isolados, respectivamente (Malavolta et al, 2009). Em Minas Gerais, Cornelio et al (2003), identificaram 14 raças em 138 isolados monospóricos de M. grisea, provenientes de 23 amostras, em que ocorreram com maior frequência as raças IA (59%), IB (16,9%) e IC (10%).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…No Estado de São Paulo, constataram-se 21 raças fisiológicas de M. grisea de um total de 71 isolados monospóricos, sendo as raças fisiológicas mais prevalentes pertencentes aos grupos IB e ID, com frequências de 32 e 30% dos isolados, respectivamente (Malavolta et al, 2009). Em Minas Gerais, Cornelio et al (2003), identificaram 14 raças em 138 isolados monospóricos de M. grisea, provenientes de 23 amostras, em que ocorreram com maior frequência as raças IA (59%), IB (16,9%) e IC (10%).…”
Section: Resultsunclassified
“…No entanto, ressalta-se que a raça IB-9 foi considerada de alta prevalência em regiões produtoras de arroz dos Estados de Goiás, do Mato Grosso, de Minas Gerais, de Rondônia, de São Paulo e de Santa Catarina (Cornelio et al, 2003;Filippi & Prabhu, 2001;Malavolta et al, 2009;Silva et al, 2009).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…], and in both hosts with mild symptoms. XauC 1609 was found to infect Swingle citrumelo under natural conditions (Jaciani et al, 2009), despite the fact that prior work suggested that only Mexican lime was susceptible to XauC (Malavolta Júnior et al, 1984). Additionally, XauC 535 and XauC 1609 were also differentiated by AFLP and BOX-PCR (Jaciani, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…Canker B is currently known to be present only in Argentina, Paraguay, and Uruguay (Civerolo, 1984); moreover, XauB may have been eradicated even from this restricted region by competition from Xcc (Chiesa et al, 2013). Canker C is limited to the state of São Paulo, Brazil (Malavolta Júnior et al, 1984); the most recent field report dates to 2009 (Jaciani et al, 2009). Xacm is the causal agent of citrus bacterial spot, which induces symptoms very similar to those of canker, but the lesions are flat and not raised.…”
Section: Introductionmentioning
confidence: 99%